Study of Measuring Heavy Metals in Some Leafy Vegetables (Comprehensive Journal of Science, 2025)
This study was conducted to assess the concentration of heavy metals in some of the most consumed leafy vegetables in the Al-Jmail area of western Libya. The heavy metals lead, cadmium, chromium, and copper were measured in some vegetables, including parsley, dill, and spinack. The values of cadmium in the parsley sample ranged from a maximum of 2.25 mg \litre  to a minimum of less than 0.3 mg. For copper, the highest value was 2.46 mg/liter and the lowest was 2.2 mg/liter. As for lead, the highest value was 14.198 mg/liter and the lowest was less than 0.3 mg. The values for chromium were equal in four lod, being less than 0.05 mg/liter.In the dill sample, the highest value for cadmium was 3.9 mg/liter, with the lowest value being less than 0.3 mg/liter. For copper, the highest value was 1.74 mg/liter and the lowest was less than 0.3 mg/liter. The highest value for lead was 15.5 mg/liter and the lowest was 10.6 mg/liter. The values for chromium were equal in all four directions, being less than 0.05 mg/liter.In the spinack sample, the highest value for cadmium was 0.75 mg/liter, with the lowest value being less than 0.5 mg/liter. For copper, the highest value was 2.11 mg/liter and the lowest was 1.25 mg/liter. The values for lead were equal in all four directions, being less than 0.03 mg/liter. The values for chromium were also equal in four lod , being less than 0.05 mg/liter.The results showed that the concentrations of heavy metals (cadmium and lead) in the parsley and dill vegetable samples were above the permissible limits according to the World Health Organization specifications from 2001.
Keywords: Heavy metals, Cadmium, Lead, Chromium, Copper, Leafy vegetables, Parsley, Dill, Spinach, Al-Jmail, Western Libya, Contamination, WHO permissible limits